Análise eletromiográfica e cinemática dos músculos do Core no exercício abdominal tradicional e com a utilização do aparelho Rock Gym® - Gregorio, Fabio Clemente (2017)
Abdominal exercises are performed with the purpose of prevention, rehabilitation of pain in the lumbar region, increased resistance and stem force for improving activities of daily living and get the aesthetic standard released by the society. The objective of this work was to analyze and compare the electrical activity of the rectus abdominis (upper [RAS] and lower [RAI]), abdominal external oblique (OE), spinal erector (EE) and Rectus Femoris (RF) during the execution of the traditional abdominal exercise and with the using the appliance Rock Gym®. The sample was selected on a non-probabilistic or convenience. The volunteers, 15 in total, were considered physically active, aged 22.47 2.26 ± years, body mass of 73.78 7.17 ± kg, height of 1.74 ± 0.05 meters and body fat percentage of 13.44 ± 4.37% and had experience in the resistance training least one year previous to this study. The electromyography data were collected during five repetitions on each abdominal exercise (traditional and Rock Gym® in RG1 RG2 RG3 RG4). Differential surface electrodes were used to capture the electromyographic signal, which was measured by the square root of the average (Root Mean Square-RMS) and standardized (RMSn) by maximum voluntary isometric contraction. The Shapiro Wilk test was used to evaluate the normality of the data, and Mauchly test, to check the sphericity. In cases where this assumption has not been taken, the Greenhouse-Hari. The repeated measures analysis of variance (ANOVA) was used to compare the mean values of RMSn of same muscles and the average values of the magnitude of hip in different exercises, the Bonferroni comparisons test was carried out in all the analyses to check where there was no difference. The main results demonstrated that the electromyographic activity of the abdominal muscles was significantly higher or similar in the traditional exercise in the comparison of the Rock Gym ® device, however, the muscle activity in the RF device was significantly higher compared to traditional exercise. In this way, it is concluded that the traditional abdominal exercise gives priority to the recruitment of the abdominal muscles while minimizing the activity of hip flexor muscles, a factor of great importance in your choice when compared to the device, especially for people who have a weak abdominal muscles and trouble in the lumbar region of the spine.